Policy Networks in Education Policy: An Empirical Study at the City and Regency Level in West Java Province, Indonesia - Rizky Ilhami (Lembaga Pengembangan Kinerja Dosen, 2025)
Policy networks play a crucial role in the development and implementation of education policies at the regional level, as they involve interaction and collaboration between government actors, educational institutions, teachers, Non-Governmental Organizations (NGOs), communities, and the private sector. This study aims to analyze the role of policy networks in education policies in cities/regencies in West Java Province and the obstacles faced in increasing their effectiveness. The study used a qualitative approach with descriptive-analytical methods. Data were collected through in-depth interviews, observations, and documentation studies of actors involved in education policies. The results show that education policy networks still face obstacles in the form of unequal distribution of resources, limited actor capacity, weak coordination between actors, regulatory barriers, and a lack of shared learning mechanisms. This study concludes that strengthening policy networks through collaborative forums, increasing actor capacity, simplifying regulations, sustainable collaborative mechanisms, and shared learning are strategic steps to increase the effectiveness of education policies at the regional level in West Java.